C-14 powered dye-sensitized betavoltaic cells. Issue 52 (4th June 2020) - Hwang, Yunju; Park, Young Ho; Kim, Hong Soo; Kim, Dae Hee; Ali, Shahzad; Sorcar, Saurav; Flores, Monica Claire; Hoffmann, Michael R.; In, Su-Il
Abstract : A dye-sensitized betavoltaic cell is developed for the first time, which utilizes radioisotopic carbon, composed of nano-sized quantum dots, and ruthenium-based dye sensitized TiO2 as electrodes. Abstract : A dye-sensitized betavoltaic cell is developed for the first time, which utilizes radioisotopic carbon, composed of nano-sized quantum dots, and ruthenium-based dye sensitized TiO2 as electrodes. In this cell, emitted beta radiations are absorbed by the dye rather than TiO2, which resulted in enhanced performance compared to the pristine betavoltaic cell.